Migration, Agricultural Expansion, and Socio-Environmental Change in Vietnam’s Central Highlands - Minh, Đức (Technium Social Sciences Journal, 2026)
The purpose of this research is to understand how migration, agricultural development, and socio-environmental dynamics work together in the Central Highlands of Vietnam. Over the last thirty years, due to state-sponsored settlement and economic migration, this area has experienced a sudden influx of people and an economic boom in agriculture. Using a mixed-methods approach involving household surveys and interviews, focus group discussions, and policy analysis in the provinces of Dak Lak, Gia Lai, and Kon Tum, this research aims to understand the socio-environmental effects and agrarian frontier reconfiguration induced by migration. The results indicate that migration has been key in the commercialization of agriculture. The cultivation of coffee and pepper has altered land use patterns, and the commercialization of agriculture, alongside providing economic incentives and promoting further integration of the region into the wider economy, has been a significant driver of growing deforestation, soil erosion, and water overexploitation. Additionally, the benefits of agrarian change have been highly unequal. Migrant farmers have greater access to land and market opportunities, while indigenous peoples have increasingly limited access to their traditional lands and forest resources. The research connects migration, agrarian transition, and political ecology to demonstrate the interplay between demographic change, land use, and the environment. The results highlight the need for enhanced land governance, more regulations on the expansion of agricultural frontiers, and stronger policies that promote both sustainable agriculture and the livelihoods of indigenous peoples.